The environmental sustainability of successful projects with different energy alternatives (Research, Society and Development, 2021)
Developed and emerging countries were put forward with challenging goals, in the commitment to projects that          encourage the generation and consumption of energy from renewable sources, in order to generate energy in a sustainable manner and with access to the entire world population. This work aims to briefly present different projects implemented in Brazil that consider as a premise the generation of renewable energy in an environmentally appropriate way. Qualitative Literature Review, considering studies in Portuguese published from 2016 to 2021.Based on the collection of studies on the implementation of renewable energy generation projects, Brazil is compared to other countries in the world already has in its energy production a large part of the meeting of the demand through energy by hydroelectric plants, but it has great potential in promoting and investing in wind, solar and biomass energy, in addition to investing in other alternatives such as geothermal energy and energy from tides. Fostering strategic policies to diversify and reduce the cost of implementing renewable energy projects and the development of projects that look for other forms of renewable energy generation in Brazil will increase the diversification of the energy matrix and the safety of this matrix, reducing impacts environmental issues.